Inclusive learning in education: bibliometric analysis - Acosta-Tzin, José Valdo (2023)
Inclusive learning in education is a crucial global issue due to its social and economic implications. This study presents a bibliometric analysis of the evolution and trends in this field, using the Scopus database. From 2015 to 2023, interest in the topic has grown exponentially, with peaks in 2020 and 2022.The United States of America leads the research, with 37 publications. The most cited papers include authors such as Lewis, K.L., Stout, J.G., Finkelstein, N.D., Cohen, G.L., Ito, T.A., Smith, J.L., Brown, E.R., Thoman, D.B., Deemer, E.D., Burgstahler, S., Hewett, R., Douglas, G., McLinden, M., Keil, S., Roberts, W.M., Newcombe, D.J., and Davids, K. According to Lotka's Law, 17 of these authors are considered the most prolific in the field. Bradford's Law highlights BMC Medical Education, Education Sciences, European Journal of Special Needs Education, Social Inclusion, and Academic Medicine as the journals with the most articles on the topic. The authors with the most co-authorships are Douglas, G; Hewett, R; and Mclinden, M. The most recurrent keywords are inclusive learning environment, inclusion, human experiment, and equity, reflecting the current lines of research in this field. In conclusion, despite significant advances in inclusive learning and educational reforms to foster equity, they still face limitations and lack of effective adaptations globally.